Characterization and stability of Kefir with addition of açaí pulp (Research, Society and Development, 2020)
Kefir is a fermented milk which can have functional properties such as intestinal regulation and increased immune resistance. The fruit addition to Kefir aggregates nutritional and sensory value to the product. The research aimed to produce Kefir added from açaí pulp and evaluate its physicochemical and sensory characteristics and its stability for 45 days. Kefir was made from milk, fermented using Kefir grains, later added with different concentrations of açaí pulp. The processing of Kefir formulations was determined through factorial design, resulting in seven tests. The independent variables were the fermentation time (24 and 48h) and the concentration of açaí pulp (10% and 30%), with acidity being the variable response. The results of the physicochemical and sensory analyzes were subjected to statistical treatment through analysis of variance (ANOVA) and the averages were compared using the Tukey test. The physicochemical parameters of the Kefir samples are in accordance with the requirements established by the legislation. The sensory attributes showed high percentages of frequency of responses in the acceptance range of the Hedonic scale for all formulations evaluated. The samples displayed good intention of purchase by the tasters. The storage period studied in 45 days presented that the formulations remained with a viable count of lactic acid bacteria, with acidity above the established by the legislation from seven days. Therefore, the produced products are potentially probiotic, with good sensory acceptance and a positive purchase attitude from consumers and stability of 45 days.